Extract Fetal ECG from Single-Lead Abdominal ECG by De-Shape Short Time Fourier Transform and Nonlocal Median - Su, Li; Wu, Hau-Tieng (Frontiers in Applied Mathematics and Statistics, 2017)
Extract fetal ECG from single-lead abdominal ECG by de-shape short time Fourier transform and nonlocal median